CRISPR-mediated promoter editing of a cis-regulatory element of OsNAS2 increases Zn uptake/translocation and plant yield in rice - Ludwig, Yvonne; Dueñas, Conrado; Arcillas, Erwin; Macalalad-Cabral, Reena Jesusa; Kohli, Ajay; Reinke, Russell; Slamet-Loedin, Inez H. (Frontiers Media, 2024)
Developing nutritious rice with a higher yield is one approach to alleviating the problem of micronutrient deficiency in developing countries, especially human malnutrition involving zinc and iron (Fe) deficiency, and achieving better adoption. The transport of micronutrients such as Fe and Zn is mainly regulated via the nicotianamine synthase (OsNAS) gene family, whereas yield is a complex trait that involves multiple loci. Genome editing via CRISPR (clustered regularly interspaced short palindromic repeat)-Cas9, focusing on the OsNAS2 promoter, particularly the deletion of the cis-regulatory element ARR1AT at position −933, was conducted for an enhanced accumulation of Zn in the grain and per plant. The results showed that our promoter editing increased Zn concentration per plant. Evidence also showed that an improved spikelet number per main panicle led to increased grain per plant. The traits were inherited in “transgene-free” and homozygous plant progenies. Further investigation needs to be conducted to validate trait performance under field conditions and elucidate the cause of the spikelet increase.